2017
DOI: 10.3892/mmr.2017.7068
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of novel peptides derived from Sepia ink: Effects on apoptosis of prostate cancer cell PC-3

Abstract: Novel prostate cancer therapeutics are in high demand. In order to identify potential therapeutic targets, protein from sepia ink was hydrolyzed by utilizing pepsin in an orthogonal array design. Pepsin hydrolysate (SH) obtained at optimal conditions exhibited the highest antitumor activity. Subsequently, a novel antitumor peptide, which was termed SHP, was isolated through ultrafiltration, gel filtration chromatography and reversed phase high‑performance liquid chromatography. The amino acid sequence of SHP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Bioactive peptides (consisting of 2–20 amino acids) are protein fragments released from protein molecules via enzymatic hydrolysis and a series of refining processes, which harbor multiple bioactivities, including immunomodulatory [4], anti-inflammatory [5], antihypertensive [6,7,8], anticancer [9], antioxidant [10,11], and antifatigue [12] activities. Recently, several immunomodulatory peptides have been purified and identified from protein hydrolysates of natural origin [13].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive peptides (consisting of 2–20 amino acids) are protein fragments released from protein molecules via enzymatic hydrolysis and a series of refining processes, which harbor multiple bioactivities, including immunomodulatory [4], anti-inflammatory [5], antihypertensive [6,7,8], anticancer [9], antioxidant [10,11], and antifatigue [12] activities. Recently, several immunomodulatory peptides have been purified and identified from protein hydrolysates of natural origin [13].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the structurally modified QPK elicited all three apoptotic pathways (mitochondrial, death receptor, and endoplasmic reticulum stress induced) . In another study, Huang et al (2017) hydrolyzed sepia ink by pepsin to produce an antiproliferative peptide (LKEENRRRRD) acting against prostate PC-3 cells. The study showed that the resultant arginine-rich peptide was time and concentration dependent for cancer cell apoptosis.…”
Section: Anticancer/antiproliferative Activitymentioning
confidence: 99%
“…In another study, Huang et al. (2017) hydrolyzed sepia ink by pepsin to produce an antiproliferative peptide (LKEENRRRRD) acting against prostate PC‐3 cells. The study showed that the resultant arginine‐rich peptide was time and concentration dependent for cancer cell apoptosis.…”
Section: Structure–activity Relationship Of Bpsmentioning
confidence: 99%
“…Study showed that the early-stage apoptotic cells of PC-3 were increased from 9% to 29% following exposure to 10-15 mg/mL SHP for 24 h by Annexin V/PI double-staining analysis. The apoptosis induced by SHP was accompanied by the down-regulation of apoptosis regulator Bcl-2, up-regulation of apoptosis regulator Bax and activation of caspase-3 and p53 [33]. A cyclomimetic peptide based on SHP, called SIO, was designed by introducing a disulfide bond to stabilize the native peptide.…”
Section: Anticancer Peptides That Activate the Intrinsic (Mitochondrimentioning
confidence: 99%